Debt Dynamics and Global Imbalances : Some Conventional Views Reconsidered - Meredith, Guy. (Washington, D.C. : International Monetary Fund, 2007)
We use a general-equilibrium model to explain the rise in global trade and payments imbalances since the mid-1990s, and then to construct adjustment paths to a steady state. Assuming that the shocks giving rise to the imbalances do not suddenly reverse, simulated movements in the U.S. trade deficit and exchange rate are smaller and more gradual than suggested by partial-equilibrium analyses. An important factor reducing the size of the adjustments is a simulated real interest rate on U.S. external liabilities that is below both the interest rate on external assets and the U.S. real economic growth rate. In addition, the adjustment takes place over an extended period without significantly raising the share of U.S. assets in foreign portfolios, in part because depreciation of the dollar requires continued foreign accumulation of U.S. assets just to keep their portfolio share constant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet